ColorPhAST: a visual rapid colorimetric assay for detecting phage-susceptibility in Escherichia coli - Estévez, Paula Gómez; Rodríguez-Villodres, Ángel; Gálvez-Benitez, Lydia; Gutiérrez, Guillermo Martín; Cisneros, José Miguel; de la Rosa, José Manuel Ortiz; Lepe, José Antonio (Frontiers in Microbiology, 2025)
The alarming increase in the prevalence of multidrug-resistant microorganisms, which in some cases has left no available treatment options, has led to a renewed interest in previously abandoned therapeutic approaches such as bacteriophage therapy. Therefore, the development of rapid methods for determining phage susceptibility will be essential in the near future because phage-based treatments could provide a viable alternative for patients with infections caused by multidrug-resistant microorganisms. In response to this need, a new test named ColorPhAST (Color Phage Activity Susceptibility Test) based on color change of red phenol has been designed to detect phage-susceptibility in just 2 h. A total of 100 Escherichia coli isolates were used to evaluate the performance of the test, 55 being resistant to the isolated phage through the double agar overlay spot assay (gold standard method). The sensitivity and specificity of the test were 95.6 and 100%, respectively. The ColorPhAST is a fast, easy-to-performed, and accurate method with great potential for identifying susceptibility to bacteriophages.